Fungal biodiversity in dairy industry and antifungal activity of lactic acid bacteria in cheese matrix - Souza, Luana Virginia (2023)
Spoilage fungi contamination in dairy industries represents an important economic problem due to spoilage of products. In addition, due to the mycotoxins produced by some fungi, it may also represent a public health problem. Considering the current demand for lesser chemical preservatives addition in foods associated to “Clean label” tendency, the application of bioprotective cultures has been widely explored as alternative. Bacteria belonging to the group of lactic acid bacteria (LAB) stand out as possible bioprotective cultures for being widely used in food processing, show antagonist activity against spoilage microorganisms, and some species recognized as GRAS (Generally Recognized As Safe) status. Thus, considering the concern with spoilage fungi in the dairy industry and the ways to prevent these contaminations, this thesis aimed to understand the biodiversity of fungi in the dairy chain and the antifungal activity of some LAB. For that, the construction of this thesis was realized in two steps: (1) 109 filamentous fungi were isolated from spoiled dairy products and dairy production environments and identified through sequencing of the internal transcribed spacer (ITS) region; (2) 52 LAB strains were tested In vitro for their antifungal potential against Aspergillus niger and Penicillium chrysogenum and LAB with the highest antifungal activity were selected for the in situ test into cheese matrix inoculated with A. niger and P. chrysogenum. As result, Penicillium and Cladosporium were the most frequent genera isolated from spoilage dairy products. Cladosporium, Penicillium, Aspergillus, and Nigrospora had high incidence in the processing environment. Four species (Hypoxylon griseobrunneum, Rhinocladiella similis, Coniochaeta rosae, and Paecilomyces maximus) were identified for the first time in dairy environments. Three phytopathogenic genera (Montagnula, Clonostachys, and Riopa) and one pathogenic fungi (R. similis) were also identified. Regarding the phylogeny, 14 families and most of the fungi belonging to the Ascomycota phylum were observed. For the antifungal activity in vitro test, 5 strains of LAB (W. confusa (W5, W8), W. paramesenteroides (W9), W. cibaria (W25), L. Plantarum (Q4C3)) had the highest antifungal effect against the target fungi. In general, the five strains had a positive antifungal effect against A. niger and P. Chrysogenum also in the in situ test; however, these strains lose, in different intensities, their antifugal activity in cheese matrix when combined with a starter culture. Thereby, we show with our study that, despite someLAB didn’t present an antifungal effect when combined with the starter culture, it is important to emphasize that these bacteria may have great antifungal potential when apply in other food matrices which don’t use a starter culture. Finally, they can be tested regarding their other diverse technological applications. Keywords: Dairy products. Antifungal activity. Spoilage fungal. Biopreservation. Biodiversity.